Emba Ndi Voondre Kyiro Kwori Ro Gboko Amiro Ro Buku Ävuoso’ba Ro (To’dina). Ta Kyikyi’ba Ro: Buku Giṛingwa 2 Alo Aza Nätu Ro - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon; Gupta, Arnab Be (2023)
This handbook in the Moru language of South Sudan is a companion to (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America.